On the possibility of using heat stored in the magma chamber of the Avachinsky volcano and the surrounding rock for heat and power supply - Fedotov S.A.; Sugrobov V.M.; Utkin I.S.; Utkina L.I. (My University, 2007)
The results of geological and geophysical studies, including recent ones, which make it possible to verify the existence of a liquid magma chamber below the Avachinsky volcano on Kamchatka, and to estimate the chamber depth and approximate dimensions, are analyzed. The heat stored in the host rock heated by the volcanic magma chamber from the time of chamber origination to the present is estimated, taking variable chamber dimensions during the process of evolution into account. The geological-geophysical prerequisites for using the thermal energy of the heated rock which surrounds the magma chamber to supply heat and power to Petropavlovsk-Kamchatskii are analyzed. The creation of an underground geothermal circulation system (fracture heat exchanger) using deep boreholes is proposed.
Keywords: 38.19.31 Геотермика; 38.37.25 Вулканология; Авачинский